Bromazepam changes performance during target shooting but does not affect the interhemispheric coupling in the theta rhythm of the electroencephalography (Research, Society and Development, 2021)
Bromazepam emulates the inhibitory effect of the neurotransmitter gamma-aminobutyric acid (GABA) and can lead to impaired visuomotor performance. However, few studies have evaluated its effects on cortical coupling in target shooting activities. The present study aimed to analyze the acute effects of bromazepam administration in a target shooting task and the EEG theta rhythm coherence between frontal, temporal, and motor cortical areas in four shooting preparation periods. Thus, a double blind, crossover study was conducted with 30 subjects under two conditions: bromazepam (6mg) and placebo, with electroencephalographic analysis to simultaneously study the theta rhythm coherence in frontal, temporal, and motor cortex in a target shooting task; and the possible interferences of bromazepam administration. Subjects in the bromazepam group showed lower performance on the task compared to placebo (p=0.001). In addition, our analysis showed decreased coherence between regions in the same hemisphere, increased theta rhythm coherence in interhemispheric regions in frontal, temporal and motor cortex at different intervals in the preparation preceding the shooting (p=0.001). The use of bromazepam may influence task execution, possibly due to neurochemical modulation, during decision making, developing shooting preparation strategies, as well as interfering with the flow of information at the level of attention during task execution.